2010
DOI: 10.1111/j.1365-2966.2009.16049.x
|View full text |Cite
|
Sign up to set email alerts
|

The quasar relation through cosmic time - II. Evidence for evolution fromz = 3to the present age

Abstract: We study the dependence of the M BH -M host relation on the redshift up to z = 3 for a sample of 96 quasars, the host galaxy luminosities of which are known. Black hole masses were estimated assuming virial equilibrium in the broad-line regions, while the host galaxy masses were inferred from their luminosities. With these data, we are able to pin down the redshift dependence of the M BH -M host relation along 85 per cent of the Universe age. We show that, in the sampled redshift range, the M BH -L host relati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
198
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(235 citation statements)
references
References 81 publications
36
198
1
Order By: Relevance
“…There have been many studies focus on the evolution of the scaling relation. For instance, Decarli et al (2010) studied a sample of 96 quasars with redshift up to 3 and found that the M BH /M host,* ratio increases by a factor of seven from z = 0 to z = 3. Merloni et al (2010) used 89 broad-line AGNs detected in the zCOSMOS survey in the redshift range 1 < z < 2.2 and found that the average black hole to host galaxy mass ratio evolves positively with redshift.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many studies focus on the evolution of the scaling relation. For instance, Decarli et al (2010) studied a sample of 96 quasars with redshift up to 3 and found that the M BH /M host,* ratio increases by a factor of seven from z = 0 to z = 3. Merloni et al (2010) used 89 broad-line AGNs detected in the zCOSMOS survey in the redshift range 1 < z < 2.2 and found that the average black hole to host galaxy mass ratio evolves positively with redshift.…”
Section: Discussionmentioning
confidence: 99%
“…We further assumed that the Mstellar -Mbh relationship does not evolve with cosmic time, which may or may not be the case (e.g. Decarli et al 2010) as selection effects and biases makes this relationship difficult to probe as redshift increases. However, such an evolution, if it exists, appears to be similar in strength to the scatter in the mass relationships at a given time.…”
Section: Dark Matter Halo Galaxy and Black Hole Growthmentioning
confidence: 99%
“…Peng et al 2006;Alexander et al 2008;Woo et al 2008;Decarli et al 2010;Kormendy & Ho 2013). To generate a starting point, we simply begin each BH at a random fraction (from 0.1 to 0.9) of its expected value (Figure 1).…”
Section: Dark Matter Halo Galaxy and Black Hole Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…For a limited number of QSOs the use of 8-10m telescope under superb seeing conditions or with adaptive optics imaging has allowed the study of quasar host at high redshift (Kotilainen et al , 2009) and/or with adaptive optics These observations allowed to trace a a first view of the cosmic co-evolution of SMBH and their host galaxies (see e.g. Decarli et al 2010Decarli et al , 2012Sanghvi et al 2014).…”
Section: Introductionmentioning
confidence: 99%